The hard way from the Beveridge to the Bismarck model of health finance: Expectations and reality in Russia - Shishkin, Sergey; Sheiman, Igor (Frontiers in Public Health, 2023)
Most post-Soviet countries have introduced mandatory health insurance (MHI) systems which completely or partially replaced national health systems known as budgetary models. In Russia, an attempt was made to introduce a competitive MHI model with multiple health insurers. The current MHI system has, however, acquired an increasing number of features inherent in the previous budgetary model. This paper analyzes the institutional characteristics and the outcomes of a new mixed model. A combination of two analytical approaches is used: (1) considering three functions of the financing system (revenue collection, pooling funds, and purchasing health care), (2) exploring three types of the model regulation (state, societal, and market). We analyze the types of regulation that are used to implement each of the three financial functions. The model has contributed to more sustainable health funding, its geographical equalization, and to service delivery restructuring, while the implementation of its purchasing function has many unsolved problems. We highlight the dilemma of the further development of the model by (a) continuing to replace the remaining market and societal regulatory mechanisms with state regulation; or (b) developing market mechanisms and thereby strengthen the impact of health insurers on the health system performance. Lessons for countries considering the transformation of their budgetary health finance model to the MHI model are presented.